PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR SOSIOLOGI - Roswita Sonia Meak; Idris Idris (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Kupang, 2026)
This study aims to improve students’ learning engagement and outcomes by implementing the Teams Games Tournament (TGT) cooperative learning model in Sociology for twelfth-grade students at SMA Negeri 7 Kupang. This research employed a Classroom Action Research (CAR) design conducted in two cycles involving 30 students. The pre-cycle results indicated that students’ engagement was relatively moderate, with an average score of 62.33, and that learning outcomes were low, with an average score of 58; most students did not meet the minimum mastery criteria. After implementing the TGT model in Cycle I, students’ engagement increased to 75.16 (good category), and the average learning outcome rose to 77.13. In Cycle II, significant improvements were observed: engagement reached 91.33 (very good), and learning outcomes improved to an average score of 94.9, with 86.67% of students achieving mastery. These findings indicate that the TGT model effectively enhances student engagement and learning outcomes through academic games, teamwork, and healthy competition. Therefore, TGT can be considered an innovative instructional strategy to improve the quality of sociology learning.